ISOLATED FAMILIAL MEDULLARY THYROID CARCINOMA AS PART OF MULTIPLE ENDOCRINE NEOPLASM (MEN-2A: Familial Medullary Thyroid Carcinoma and Men-2a - Sharif, Dr Muhammad Ashraf; Mahmood, Asad; Murtaza, Badar; Asghar, Zunera (Pakistan Armed Forces Medical Journal, 2010)
Medullary carcinoma of the thyroid (MTC) is a distinct thyroid carcinoma that originates from the parafollicular C cells of the thyroid gland which produce calcitonin. MTC has a genetic association with multiple endocrine neoplasia (MEN) type 2A and 2B syndromes. Sporadic, or isolated, MTC occurs in 75% of patients1.